2021
DOI: 10.3389/fphar.2021.710169
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolate Ameliorates Osteopenia and Improves Bone Quality in Prednisone-Treated Rheumatoid Arthritis Rats by Regulating RANKL/RANK/OPG Signaling

Abstract: Rheumatoid arthritis (RA) is closely associated with periarticular osteopenia and leads to a high risk of generalized osteoporosis. Although glucocorticoid (GC) treatment ameliorates joint degradation and manages inflammation in RA, GC application may induce further bone quality deterioration in RA patients. Current treatments for RA lack relevant strategies for the prevention and treatment of osteopenia in RA. In this study, we aimed to investigate whether salvianolate treatment ameliorated osteopenia in pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…As per past reports, it can induce apoptosis in a variety of tumor cells, including osteosarcoma cells, without affecting most human cell types (Gamie et al 2017 ; Pan et al 2013 ). The research by Yen et al proved that TRAIL triggered osteoclast differentiation via a (necrosis factor receptor-associated factor-6) TRAF-6 dependent signal pathway, as also confirmed (Gao et al 2021 ; Yen et al 2012 ). Other experiments confirmed that microgravity induced the TRAIL expression in preosteoclast cells and promoted osteoclast differentiation (Sambandam et al 2016 ).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…As per past reports, it can induce apoptosis in a variety of tumor cells, including osteosarcoma cells, without affecting most human cell types (Gamie et al 2017 ; Pan et al 2013 ). The research by Yen et al proved that TRAIL triggered osteoclast differentiation via a (necrosis factor receptor-associated factor-6) TRAF-6 dependent signal pathway, as also confirmed (Gao et al 2021 ; Yen et al 2012 ). Other experiments confirmed that microgravity induced the TRAIL expression in preosteoclast cells and promoted osteoclast differentiation (Sambandam et al 2016 ).…”
Section: Introductionmentioning
confidence: 71%
“…In addition, Tetrandrine inhibited TRAIL expression. Past articles have confirmed that decreased TRAIL can inhibit the differentiation of osteoclasts by inhibiting TRAF6 recruitment and ultimately inhibiting the activation of the NF-κB pathway (Gao et al 2021 ). Moreover, we confirmed that the upregulation and downregulation of TRAIL expression in BMMs promoted and inhibited osteoclastogenesis, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Gao, et al. ( 58 ) demonstrated rheumatoid arthritis induced bone loss and bone quality deterioration, with high bone turnover in collagen-induced arthritis (CIA) rats. The CIA rats showed higher levels of IL-6, and TNF-α in serum accompanied by decreased mRNA and protein levels of Osx (Osterix), OPN which is induced by a TNF-α-induced inflammatory medium in vitro .…”
Section: Opn Involves Inflammation In Oa and Opmentioning
confidence: 99%
“…Gao et al. ( 58 ) found salvianolic treatment ameliorated osteopenia and improved bone quality in rats, the potential mechanism may rely on increasing Osx, OPN, and Col1a1 levels in TNF-α-induced MC3T3-E1 osteoblasts through regulating the RANKL/RANK/OPG signaling pathway. Monotropein was also found to play an important role in regulating the OPN metabolism in MC3T3-E1 cells.…”
Section: Pharmaceutical Interventions Of Opn In Oa and Opmentioning
confidence: 99%
“…The results showed that SAC can promote osteogenic differentiation through the AMPK/SIRT1 pathway. At present, studies have shown that salvianolic acid esters improve osteopenia and bone mass in prednisone‐treated rheumatoid arthritis rats by regulating the RANKL/RANK/OPG signaling pathway, 24 but no study has investigated the effects of SAC on the AMPK/SIRT1 signaling pathway. There are also studies showing that salvianolic acid B can prevent bone loss, 25 but whether SAC also has this effect has not been clarified.…”
Section: Discussionmentioning
confidence: 99%